Neoadjuvant immunotherapy plus chemotherapy for resectable non-small cell lung cancer with driver mutations: a retrospective analysis - Xu, Junhao; Yao, Jinquan; Geng, Yuxin; Huang, Jie; Zou, Bingwen; Sun, Xiao; Yu, Jinming; Teng, Feifei (Frontiers in Immunology, 2025)
BackgroundNeoadjuvant immunotherapy combined with chemotherapy offers significant benefits for patients with resectable non-small cell lung cancer (NSCLC). However, its efficacy and safety in patients harboring driver gene mutations remain unclear. This study aimed to assess the real-world efficacy and safety of neoadjuvant immunotherapy plus chemotherapy in resectable NSCLC with and without driver gene mutations.MethodsWe retrospectively analyzed patients with NSCLC who received neoadjuvant immunotherapy plus chemotherapy followed by surgical resection. Efficacy was evaluated based on the best radiological response (BRR), major pathologic response (MPR), and pathological complete response (pCR). Survival outcomes were assessed using event-free survival (EFS), and safety was evaluated in all patients.ResultsThe study included 73 patients, comprising 34 with driver gene mutations and 39 without driver gene mutations. During the neoadjuvant therapy phase, the BRR rate was 58.8% in the mutated group and 66.7% in the wild-type group (p = 0.489). The MPR rate was 47.1% in the mutated group and 41.0% in the wild-type group (p = 0.604). The pCR rates were 32.4% and 33.3%, respectively (p = 0.929). No significant differences were observed in EFS between the mutated and wild-type groups (p = 0.83). Grade 3 treatment-related adverse events occurred in 11.8% of patients with driver gene mutations and 17.9% of patients without driver gene mutations; no Grade 4 or 5 adverse events were reported.ConclusionNeoadjuvant immunotherapy plus chemotherapy remains a promising treatment option for patients with resectable NSCLC, irrespective of genetic mutation status.